Innovative Solutions for the Rehabilitation of Bridges Using Flexible Galvanized Steel Structures: A Case Study - Doinea Negrea; Christiana Emilia Cazacu; Mircea Contiu (MDPI Sustianability, 2023)
The objective of the project was the rehabilitation and expansion of one bridge, located on the DN28 (a national road) in Sarca, Iasi County. The solution includes an atypical use of the flexible galvanized steel structure. The main challenge in this case was to finish the works without any traffic interruption on this section of the national road, as well as the assembly of the said corrugated steel structure under the existing bridge. The work was executed in record time and with reduced costs in comparison with the classic alternative solutions, such as concrete bridges. The paper highlights practical aspects from the key moments of the project and presents the major challenges and how they were solved for both the design and the construction stages.
Keywords: flexible steel structures; corrugated steel plates